IPTEKS ESTIMASI BIAYA BAGI USAHA KECIL MENENGAH DALAM PERENCANAAN BIAYA - Budiarso, Novi Swandari (Universitas Sam Ratulangi, 2019)
Small and medium enterprise has been growing fast in Manado City and has its own markets and also create its competitive advantage. Most of government programs are reflect the effort to support small and medium enterprise in term to increase the wealth of Indonesian people. Some of problems faced by small and medium enterprise are relate to managerial problem, such as administration and financial reporting. Moreover, limited of knowledge about management technology for the owners of small and medium enterprise plays the role in case to take decision on running business. High-low method is one of managerial tool to make cost estimation which help the owners to make decision such as cost planning.Â